Improvement of Frozen Fishball Quality : The Role of Starch and Fat - Wunwiboon Garnjanagoonchorn; Phimonphan Hunpaisal (Agriculture and Natural Resources, 1994)
The improvement of fishball quality by adding starch and/or pork back fat showed that frozen fishballs with the addition of 5% tapioca or modified starch had no statistical significant difference ingel strength values and sensory scores. However the addition of different levels of fat caused significant difference (P<0.05) in gel strength values, the higher the fat content the lower the gel strenght value. During 12 weeks of frozen storage at -18°C, fishballs with the addition of 5% tapioca or modified starch plus 4-8% pork back fatremained acceptable by sensory panels. Scanning electron microscope (SEM) was used to study the microstructure of comminuted fish meat prepared at different steps of the fishball process. Micrograph of batter, chopped with salt, starch and pork back fat showed the interconnected network of protein matrix. Cooking the fish batter caused the matrix to become more aggregated and occurred as opaque gel, and the fat globules were bound to the protein gel matrix.